Atomically Dispersed Metal‐Based Catalysts for Zn–CO2 Batteries. Issue 12 (15th September 2022) - Gao, Sanshuang; Wei, Tianran; Sun, Jiaqiang; Liu, Qian; Ma, Dui; Liu, Wenxian; Zhang, Shusheng; Luo, Jun; Liu, Xijun
Abstract : Rechargeable aqueous Zn–CO2 batteries show great promise in meeting severe environmental problems and energy crises due to their combination of CO2 utilization and energy output, as well as advantages of high theoretical energy density, abundant raw materials, and high safety. Developing high‐efficiency and stable CO2 reduction reaction (CO2 RR) electrocatalysts is of critical importance for the promotion of this technology. Atomically dispersed metal‐based catalysts (ADMCs), with extremely high atom‐utilization efficiency, tunable coordination environments, and superior intrinsic catalytic activity, are emerging as promising candidates for Zn–CO2 batteries. Herein, some recent developments in atomically dispersed metal‐based catalysts for Zn–CO2 batteries are summarized, including transition metal and non‐transition metal sites. Moreover, various synthetic strategies, characterization methods, and the relationship between active site structures and CO2 RR activity/Zn–CO2 battery performance are introduced. Finally, some challenges and perspectives are also proposed for the future development of ADMCs in Zn–CO2 batteries. Abstract : This minireview summarizes some recent advances in atomically dispersed metal‐based catalysts for Zn–CO2 batteries, with emphasis on synthetic strategies, structural characterization, and structure‐performance relationships.